Establishment of a Surgery-Induced Osteoarthritis Rat Model - Lin, Yu-Hsing; Tsai, Wei-Huang; Chiu, Hsuan-Wen; Chiu, Ching-Feng; Chiu, Chien-Chao; Lu, Yen-Jung; Wu, Tsung-Han; Huang, Ping-Min; Chen, Guan-Hong; Lin, Chia-Yu; et al. (British Journal of Healthcare and Medical Research, 2022)
The degenerative arthritis has been a common knee joint disease in Taiwan. In mild cases of degenerative arthritis, it may just be a little uncomfortable to walk, but severe degenerative arthritis will cause difficulty in walking and even loss of basic mobility. The loss of articular cartilage in degenerative arthritis is irrecoverable. Currently, the degeneration of the knee joint can be easily divided into three levels based on its severity: primary, intermediate, and severe. The choice of treatments for degenerative arthritis will vary in according to different levels that is mainly divided into the non-surgical treatment and surgical treatment. Therefore, how to prevent knee joint degeneration is an important issue. In this study, anterior cruciate ligament transection (ACLT) plus medial meniscectomy (MMx) surgery were used to established a rat model with degenerative arthritis. According to all data, we have successfully established a rat model with degenerative arthritis via ACLT-MMx surgery. We wish this model will applied on the research of degenerative arthritis drugs and the design of therapeutic strategies for degenerative arthritis in the future.